The effects of tDCS on the processing of peri-personal space while adapting to different virtual environments - Thair, Hayley (2017)
In a series of 6 experiments this thesis aimed to explore how the processing of peri-personal space might be affected by changes in sensory information. Previous research has shown that when stimuli is presented within peri-personal space it is processed differently, specifically it has been suggested that there is a prioritisation of space to the area around the hands. If there is a change in processing for the space around us, how might this be affected when interacting with a virtual or augmented environment in which sensory information may be altered? To investigate these changes the MIRAGE mediated reality system was used in which a live video recording of the hand is displayed in real-time in its spatially veridical location, and allows the manipulation of this image and sensory modalities separately. This allowed a more detailed evaluation of previous theories by testing spatial, temporal, and fidelity changes to the hand. Results showed spatial changes between seen and felt hand positions to significantly alter the processing of stimuli presented near and far from the hands. Specifically it was illustrated that a gradual separation between the visual and real hand locations seemed to first create an expansion in the visual receptive fields of bimodal visual-tactile neurons, and second, suggested a remapping of the limbs location to somewhere between the separate representations. Furthermore the application of transcranial direct current stimulation (tDCS), specifically cathodal stimulation, appears to have disrupted proprioceptive feedback, however these effects require further investigation and replication. Results also showed how temporal lag can impair performance on a movement task, while changes in hand fidelity did not significantly alter the processing of peri-personal space. In summary, the experiments presented in this thesis illustrate that spatial changes between seen and felt hand positions significantly alter the way we process space around the hands, and suggest that previous theories need to be re-evaluated and possibly combined to better represent how these changes occur. The findings also have implications for which factors may be most important when exploring how we process peri-personal space in an augmented or virtual environment.